WZW-like action for heterotic string field theory - Berkovits, Nathan [UNESP]; Okawa, Yuji; Zwiebach, Barton (Springer Nature, 2004)
We complete the construction of the Neveu-Schwarz sector of heterotic string field theory begun in [9] by giving a closed-form expression for the action and gauge transformations. Just as the Wess-Zumino-Witten (WZW) action for open superstring field theory can be constructed from pure-gauge fields in bosonic open string field theory, our heterotic string field theory action is constructed from pure-gauge fields in bosonic closed string field theory. The construction involves a simple alternative form of the WZW action which is consistent with the algebraic structures of closed string field theory. © SISSA/ISAS 2004.
Keywords: String Field Theory; Superstrings and Heterotic Strings